2006
DOI: 10.1080/08916930500485002
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cardiac autoimmunity in Chagas heart disease: A case for molecular mimicry

Abstract: Up to 18 million of individuals are infected by the protozoan parasite Trypanosoma cruzi in Latin America, one third of whom will develop chronic Chagas disease cardiomyopathy (CCC) up to 30 years after infection. Cardiomyocyte destruction is associated with a T cell-rich inflammatory infiltrate and fibrosis. The presence of such lesions in the relative scarcity of parasites in the heart, suggested that CCC might be due, in part, to a postinfectious autoimmune process. Over the last two decades, a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 182 publications
1
84
0
11
Order By: Relevance
“…However, in order to definitively "prove" molecular mimicry occurs, it must be demonstrated that a single antigen receptor (T cell or antibody) reacts with epitopes of both the parasite and the host and can promote tissue inflammation. The first element crossreactivity of a T cell clone with parasite and host peptides has been demonstrated, but the second has not [54,58].…”
Section: Parasite-induced Autoimmunitymentioning
confidence: 99%
“…However, in order to definitively "prove" molecular mimicry occurs, it must be demonstrated that a single antigen receptor (T cell or antibody) reacts with epitopes of both the parasite and the host and can promote tissue inflammation. The first element crossreactivity of a T cell clone with parasite and host peptides has been demonstrated, but the second has not [54,58].…”
Section: Parasite-induced Autoimmunitymentioning
confidence: 99%
“…One of the most accepted explanations claims that chronic cytokine production in the heart is responsible for most of the observed cardiac alterations. 2,11 Clinical studies and animal models have shown that right and left ventricles are compromised during the time course of Chagas disease. 3,[8][9][10][12][13][14][15] It is already known that right ventricle function is dysregulated during Chagas disease, however, few studies have pointed out which molecular mechanisms are responsible for right ventricular myocyte dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is based on the apparent absence of parasites in cardiac inflammatory lesions and the presence of anti-self immune responses in chronic Chagas cardiomyopathy patients, caused by either autoantibodies or autoreactive T cells, derived by molecular mimicry between parasite and host antigens , Girones et al 2005. This supposition suggested that etiologic treatment would be of little benefit (Cunha-Neto et al 2006).…”
mentioning
confidence: 99%